Emergency, anaesthetic and essential surgical capacity in the Gambia - Adam Iddriss; Nestor Shivute; Stephen Bickler; Ramou Cole-Ceesay; Bakary Jargo; Fizan Abdullah; Meena Cherian (The World Health Organization, 2011)
OBJECTIVE: To assess the resources for essential and emergency surgical care in the Gambia. METHODS: The World Health Organization's Tool for Situation Analysis to Assess Emergency and Essential Surgical Care was distributed to health-care managers in facilities throughout the country. The survey was completed by 65 health facilities - one tertiary referral hospital, 7 district/general hospitals, 46 health centres and 11 private health facilities - and included 110 questions divided into four sections: (i) infrastructure, type of facility, population served and material resources; (ii) human resources; (iii) management of emergency and other surgical interventions; (iv) emergency equipment and supplies for resuscitation. Questionnaire data were complemented by interviews with health facility staff, Ministry of Health officials and representatives of nongovernmental organizations. FINDINGS: Important deficits were identified in infrastructure, human resources, availability of essential supplies and ability to perform trauma, obstetric and general surgical procedures. Of the 18 facilities expected to perform surgical procedures, 50.0% had interruptions in water supply and 55.6% in electricity. Only 38.9% of facilities had a surgeon and only 16.7% had a physician anaesthetist. All facilities had limited ability to perform basic trauma and general surgical procedures. Of public facilities, 54.5% could not perform laparotomy and 58.3% could not repair a hernia. Only 25.0% of them could manage an open fracture and 41.7% could perform an emergency procedure for an obstructed airway. CONCLUSION: The present survey of health-care facilities in the Gambia suggests that major gaps exist in the physical and human resources needed to carry out basic life-saving surgical interventions.